Association of circulating Progesterone Receptor Membrane Component-1 (PGRMC1) with PGRMC1 expression in breast tumour tissue and with clinical breast tumour characteristics. (October 2020) - Cai, Guiju; Yang, Xue; Ruan, Xiangyan; Wang, Jing; Fang, Yi; Wei, Yun; Zhang, Ying; Gu, Muqing; Mueck, Alfred O.
Highlights: For the first time PGRMC1 in blood and tissue of breast cancer patients was assessed. Increased blood PGRMC1 is associated with PGRMC1 expression in breast cancer tissue. Blood PGRMC1 is positively associated with tissue PGRMC1, ER and cancer stage. Blood PGRMC1, as a new tumour marker, may be superior to CEA, CA125, CA153 and TPS. A "cut-off value" is calculated for the use of PGRMC1 as a predictor of poor prognosis. Abstract: Objectives: Progesterone receptor membrane component-1 (PGRMC1) in breast cancer tissue has been suggested to predict a worse prognosis. The aim of this study was to assess for the first time whether PGRMC1 expressed in cancer tissue is associated with PGRMC1 blood concentrations and whether both are correlated with clinical tumour characteristics known to predict a worse outcome. Methods: In total, 201 patients with invasive breast cancer and 65 with benign breast disease (control group) were recruited. PGRMC1 blood concentrations were measured by a recently developed ELISA, PGRMC1 in breast cancer tissue was assessed by immunohistochemistry, and the correlation between the two was calculated. Receiver-operating characteristic (ROC) curve analysis was used to assess area under the curve (AUC). Furthermore, PGRMC1 was correlated with tumour characteristics such as tumour diameter, tumour grade and metastatic status, and with known blood tumour markers. Results: AUC for the breast cancer group was 0.713, which was significantly higher than in the control group ( p < 0.01). Blood PGRMC1 concentrations had a strong (positive) correlation with tissue PGRMC1 expression ( p < 0.01) but were not associated with serum tumour markers CEA, CA125, CA153 and TPS. Tissue PGRMC1, ER and cancer stage were positively associated with blood PGRMC1 ( p < 0.05). Conclusions: As PGRMC1 expression levels in cancer tissue were significantly correlated with PGRMC1 in blood, and because concentrations in blood were also positively associated with breast tumour characteristics known to predict a worse prognosis, PGRMC1 may be valuable as a new tumour marker and may be superior to known tumour markers such as CEA, CA125, CA153 and TPS.